Role of Insect Gut Microbiota in Pesticide Degradation: A Review - Siddiqui, Junaid Ali; Khan, Muhammad Musa; Bamisile, Bamisope Steve; Hafeez, Muhammad; Qasim, Muhammad; Rasheed, Muhammad Tariq; Rasheed, Muhammad Atif; Ahmad, Sajjad; Shahid, Muhammad Ibrahim; Xu, Yijuan (Frontiers in Microbiology, 2022)
Insect pests cause significant agricultural and economic losses on crops worldwide due to their destructive activities. To survive, these insects are able to resist dangerous substances introduced by humans in the form of insecticides. Pesticides may have unintended harmful impacts on non-target creatures, humans, and the environment. As pesticides are designed to be poisonous and are intentionally released into the environment. According to new research, microbes that live in insect symbioses have recently been found to protect insects against toxins. Symbioses have been formed among the pest and various types of microbes, which is a defensive mechanism against pathogens and pesticides. Insect guts provide unique conditions for microbial colonization, and bacteria in the stomach can deliver numerous benefits to their hosts. Insects vary significantly in their reliance on gut microbes for basic functions. Insect digestive tracts are very different in shape and chemical properties, which have a big impact on the structure of the microbial community. Insect gut microbiota has been found to contribute to feeding, parasite and pathogen protection, immune response modulation, and pesticide breakdown. Our study will examine the role of gut microbiota in pesticide detoxification and the mechanisms behind the development of resistance in insects to various pesticides. To better understand detoxifying microbiota in agriculturally significant pest insects, we provided comprehensive information regarding the role of gut microbiota in the detoxification of pesticides.